Green building outdoor thermal comfort in hot-desert climatic region. Issue 1 (31st December 2022) - Elshafei, Ghada; Katunský, Dušan; Zeleňáková, Martina; Negm, Abdelazim
Abstract: This paper studies the Egyptian building design strategies for different building envelope shapes based on the green building design using the DesignBuilder program by simulating the outdoor climate conditions depending on the Egyptian meteorological data. The simulated results are applied to Minia City as one of the hot-desert climate regions in Egypt. The research is performed on the hottest day in summer according to the analysis of climatic data overall months using the climate consultant tool. This research studies two main variables to characterize the quantitative relationships between the building form and the Natural Ventilation (NV) of thermal comfort to be achieved, which are mixed-mode maximum wind speed, and natural ventilation setpoint temperature. The research focuses on two output parameters, which are air velocity and pressure, relating to natural outdoor ventilation. The simulation findings revealed that the circle form offers the best case, which has a significant role in achieving thermal comfort that optimized the value between the two major parameters in building design, while the worst case is the U-shaped building based on the same two optimized values. Finally, the usage of natural ventilation, simultaneously with choosing the suitable building geometry, is principal for adapting the current outdoor air velocity and pressure, thus reducing the energy consumption of buildings. Practical application : This paper studies the relationship between building form and natural ventilation to achieve outdoor thermal comfort and its effects on buildings. The study assesses the wind speed and temperature parameters using the DesignBuilder tool. The study suggests a combination between natural ventilation and choosing the suitable building form to adapt the air velocity and pressure to reduce the energy consumption of the buildings.